(untitled) (Research, Society and Development, 2024)
Objective: To study the epidemiological profile validation of the epidemiological profile of hospitalized people with essential arterial hypertension in the northern health of Brazilian Maranhão State. Methodology: We did a descriptive epidemiological study using secondary data on arterial hypertension available in the Department of Informatics of the Unified Health System (DATASUS). Results: 44,786 hospitalizations for essential hypertension happened in northern of the State of Maranhão. Between the rate of hospitalized patients by sex, the highest percentage for women was 61%. Most recently, the age recorded was of patients between 60 and 79 years, representing 42% of all patients. The highest average hospital stays, and daily expenses are due to the Health Region/municipio São Luís, representing an average of 5.8 days with an average hospitalization value of R610.88. The brown patients are due to the largest population registered with morbidity. Final Considerations: I have observed that in national and international literature there are divergences in the relationship between sex and essential hypertension, however, it has been explained that the female sex has a contrast in the development of Systemic Arterial Hypertension (HAS), once it has been done several times. A Genetic and phenotypic disposition for the growth of talent in this sex. Primary health care becomes important in locating and not accompanying patients with SAH or those bordering on arterial pressure so that the secondary system does not “suffocate”, causing no expenses, that are passive to minimize.